2021
DOI: 10.1097/cm9.0000000000001550
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome in China: a review on the epidemiology, diagnosis, and management

Abstract: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disease worldwide. Current guidelines of IBS are mostly based on the western populations and expected to vary in different communities. China has a large population and a vast literature is available on IBS. Due to linguistic variations in the literature, the studies are not widely known and their conclusions thus remain largely obscured to the western medical literature. In this article, we reviewed the published literatures on the investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…Irritable bowel syndrome with diarrhea (IBS-D), a subtype of IBS characterized by abdominal discomfort and frequent defection, is the most prevalent functional gastrointestinal disorder (FGID) both in China and globally ( Liu and Liu, 2021 ; Sperber et al, 2021 ). Anti-diarrheal medications such as anticholinergics, mu-opioid agonists, and serotonin receptor antagonists are still widely used in IBS-D therapy but have mixed efficacy and can cause side effects ( Camilleri and Andresen, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Irritable bowel syndrome with diarrhea (IBS-D), a subtype of IBS characterized by abdominal discomfort and frequent defection, is the most prevalent functional gastrointestinal disorder (FGID) both in China and globally ( Liu and Liu, 2021 ; Sperber et al, 2021 ). Anti-diarrheal medications such as anticholinergics, mu-opioid agonists, and serotonin receptor antagonists are still widely used in IBS-D therapy but have mixed efficacy and can cause side effects ( Camilleri and Andresen, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, heterogeneity depending on cities (3.2% in Xi’an, 5.9% in Hangzhou, 7.6% in Changzhou, and 15.8% in Shanghai) was observed. 25 A meta-analysis suggested that a history of acute gastrointestinal infection, food allergies, alcohol consumption, and anxiety/depression were significant IBS risk factors among the Chinese. 26 Whether our observation of low IBS prevalence in Beijing was due to regional heterogeneity or some underlying factors is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the differences in survey samples and survey criteria, multiple research studies have shown that the incidence of IBS in China varied from 4.5% to 12.7%. [7][8][9] As early as 2013, a study showed that the direct medical expenses for an IBS patient in the United States could reach up to US$7547 per year. [10] In China, the total annual medical service cost for IBS patients was US$2 RHW and YKL contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%